2015
DOI: 10.1139/cjfas-2014-0320
|View full text |Cite
|
Sign up to set email alerts
|

Influence of wind, wave, and water level dynamics on walleye eggs in a north temperate lake

Abstract: Walleye (Sander vitreus) populations are cyclic because of biotic and abiotic factors, and wind activity, wave energy, and water levels may be influential given walleye spawn close to shore. We installed an anemometer and tridirectional velocimeter on a spawning reef in Big Crooked Lake, Wisconsin, in 2005 to determine wind-wave relationships and wave energy exceedance of critical velocities of both egg (affecting transport) and substrates (affecting abrasion or burial). To evaluate egg movement, we delineated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In contrast to Day's (1991) study of Walleye larvae in the Muskegon River during 1986, we observed significantly lower densities of Walleye larvae at the downriver site (Maple Island Road) than at sites further upstream in both years. Walleyes are known to spawn on gravel-cobble substrates (Raabe and Bozek 2015), which are found primarily upstream of the Thornapple site, rather than on sandy substrates, which are common in the lower river. We cannot explain why Day (1991) found higher catches of Walleye larvae at the Maple Island Road site than at upstream sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to Day's (1991) study of Walleye larvae in the Muskegon River during 1986, we observed significantly lower densities of Walleye larvae at the downriver site (Maple Island Road) than at sites further upstream in both years. Walleyes are known to spawn on gravel-cobble substrates (Raabe and Bozek 2015), which are found primarily upstream of the Thornapple site, rather than on sandy substrates, which are common in the lower river. We cannot explain why Day (1991) found higher catches of Walleye larvae at the Maple Island Road site than at upstream sites.…”
Section: Discussionmentioning
confidence: 99%
“…Walleye reproductive success and potential recruitment are known to be influenced by biotic and abiotic factors occurring during the egg and larval stages. Abiotic factors-primarily river flow and temperature-are known to affect the production and survival of Walleye eggs and larvae, with higher discharges and colder temperatures decreasing egg and larval survival and abundances (Mion et al 1998;Ivan et al 2010;Crane and Farrell 2013;DuFour et al 2014;Raabe and Bozek 2015). Cold water temperatures can delay egg development and can reduce survival through increased exposure to predation or disease.…”
mentioning
confidence: 99%
“…The present results are also consistent with other models demonstrating the occurrence of silt deposition in areas of low wave energy (Rasmussen and Rowan 1997;Hakanson and Jansson 2002). Higher critical velocity thresholds for large substrates (Raabe and Bozek 2015) reduce their erosion potential along shorelines where wind-wave energy may be sufficient to move silt, sand, or gravel substrates.…”
Section: Discussionmentioning
confidence: 99%
“…However, these models were focused on predicting coarse‐ and fine‐grained substrates throughout their systems, with little information regarding the nearshore area. Raabe and Bozek () documented water velocities high enough to transport nearshore sediments in Big Crooked Lake, Wisconsin. These measurements were correlated to wind velocity measurements from the same location (Raabe and Bozek ).…”
mentioning
confidence: 99%
“…Raabe and Bozek () documented water velocities high enough to transport nearshore sediments in Big Crooked Lake, Wisconsin. These measurements were correlated to wind velocity measurements from the same location (Raabe and Bozek ). This suggests that wind has the ability to influence nearshore substrate composition within lakes, a hypothesis shared by Schall et al (2017).…”
mentioning
confidence: 99%